2018
DOI: 10.1515/gps-2017-0033
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for the polymerization of tetraphenyltetramethylcyclotetrasiloxane by an environmentally friendly catalyst called Maghnite-H+

Abstract: This work is devoted to the study of the cationic ring opening polymerization of tetraphenyltetramethylcyclotetrasiloxane (D4Ph,Me), using a solid green catalyst prepared by the activation of a natural clay by sulfuric acid (Maghnite-H+). This treatment leads to the spacing of the montmorillonite sheets due to the substitution of the existing interlayer cations by the protons of the acid. This consequence is clearly shown on the X-ray diffraction (XRD) spectrum. The polymerization reaction proceeded in bulk an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This non-toxic cation initiator has emerged as an efficient initiator for olefin monomer polymerization, offering a promising alternative to heavy metal-containing initiators (such as SnCl 4 , AlCl 3 , TiCl 4 , etc). [56][57][58][59][60][61] In 2011, Malika Chabani utilized Maghnite-H + as a initiator for bulk cationic polymerization of 2-chloroethyl vinyl ether (CEVE). 62 The study found that the polymerization in dichloromethane or toluene solution yielded higher molecular weight and narrower molecular weight distribution (MWD) (Figure 5).…”
Section: Maghnite-h + Novel Solid Initiator Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…This non-toxic cation initiator has emerged as an efficient initiator for olefin monomer polymerization, offering a promising alternative to heavy metal-containing initiators (such as SnCl 4 , AlCl 3 , TiCl 4 , etc). [56][57][58][59][60][61] In 2011, Malika Chabani utilized Maghnite-H + as a initiator for bulk cationic polymerization of 2-chloroethyl vinyl ether (CEVE). 62 The study found that the polymerization in dichloromethane or toluene solution yielded higher molecular weight and narrower molecular weight distribution (MWD) (Figure 5).…”
Section: Maghnite-h + Novel Solid Initiator Systemmentioning
confidence: 99%
“…The separated Maghnite‐H + initiator can be recycled and reused. This non‐toxic cation initiator has emerged as an efficient initiator for olefin monomer polymerization, offering a promising alternative to heavy metal‐containing initiators (such as SnCl 4 , AlCl 3 , TiCl 4 , etc) 56–61 …”
Section: Green Initiation System For Cationic Polymerizationmentioning
confidence: 99%
“…Maghnite has acid sites of Brönsted and Lewis type. These active sites responsible for priming chemical reactions can be created by binding high charge density cations such as protons on the surface of layers [18][19][20]. Proton-loaded maghnite has been successfully used as a heterogeneous catalyst for many polymerization reactions [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical and physical properties of the mineral clay depend strongly on the amount of water present between the layers. Clay minerals have catalytic properties in the polymerization reactions of several cyclic and siloxane monomers due of the surface acidity, which have been the subject of huge number of studies [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%